Solvation, Rational Design, and Interfaces: Development of Divalent Electrolytes - Leon, Noel J.; He, Mingfu; Liao, Chen (Frontiers in Energy Research, 2022)
Rechargeable multivalent ion batteries are promising tools to complement current lithium-ion batteries for a future of diverse energy storage needs. Divalent Mg and Ca are attractive candidates for their high crustal abundance, high volumetric anode capacity, and infrequent dendrite formation during electrochemical cycling. Electrolyte research is central to these efforts and continually improves coulombic efficiencies towards the ideal 100%. This mini-review discusses recent work towards fundamental understandings that push these chemistries towards practical use. Piecing together compatible cathode and electrolytes for a complete practical multivalent ion battery lacks a cohesive method for further development and refinement. Understanding liquid solvation, utilizing rational design, and probing interfacial interactions are focal points that govern electrolyte performance. The combination of these areas will be critical for meaningful development.